Has Distance Died? : Evidence from a Panel Gravity Model - Brun, Jean-Francois; Carrere, Celine; Guillaumont, Patrick; de Melo, Jaime (Published by Oxford University Press on behalf of the World Bank, 2014)
The estimated coefficient of distance on the volume of trade is generally found to increase rather than decrease through time using the traditional gravity model of trade. This distance puzzle proved robust to several ad hoc versions of the model using data for 1962-96 for a large sample of 130 countries. The introduction of an augmented barrier to trade function removes the paradox, yielding a decline in the estimate of the elasticity of trade to distance of about 11 percent over the 35-year period for the whole sample. However, the death of distance is shown to be largely confined to bilateral trade between rich countries, with poor countries becoming marginalized.